Obtaining cellulases against oil palm empty fruit bunch from a metagenomic library (2012)
Palm growing is one of the most promising and important agricultural sectors in Colombia. However the increment in the palm oil production has resulted in the generation of millions of tons of wastes as empty fruit bunch. Given this, it is important to generate new uses for this subproduct. One of the alternatives is the simplification of cellulose content of the empty fruit bunch in fermentable sugars as cellobiose and glucose, for a subsequent carburant alcohol production. The degradation of cellulose requires enzymes named cellulases that have the capability to hydrolase glycosidic bonds from cellulose. This study focuses on identify and characterize cellulases active against oil palm empty fruit bunch from a metagenomic library. A functional screening of the library, alloed to select four clones with the ability to degrade cellulose. The effect of pH, temperature and ion metals over the cellulases extracted from the positive clones was evaluated.